Early Palaeolithic Cultural Facies and the Levalloisian at Baker's Hole - Francis Wenban-Smith (Papers from the Institute of Archaeology, 1992)
The purpose of this short paper is to use the lithic material recovered from the site of Baker's Hole to demonstrate the point that the classificatory framework generally in operation for British, and also other European, Early Palaeolithic lithic material is overly simplified. The pigeon-holing of assemblages into one of a restricted number of industrial variants, or cultural facies, based on the presence and relative predominance of selected tool-types or knapping techniques, has served to obscure the variety and complexity of Early Palaeolithic lithic technology. The particular lithic industrial variant discussed in this paper is the Levalloisian.
Keywords: Palaeolithic; levallois; technology